REHYDRATION KINETICS OF DEHYDRATED BERRIES - Ígor H. de M. R. Ciolin; Camila W. Antunes; Daiane C. Lenhard; Carolina C. Garcia (Engenharia Agrícola, 2021)
ABSTRACT Cranberries and blueberries are small fruits known for their antioxidant properties. However, due to their high water content and short shelf life, they are generally marketed as dehydrated berries. The present work aimed to model the rehydration of dehydrated berries. Rehydration tests were conducted at 7 and 29°C using milk as a solvent and at 7, 29, and 45°C when the solvent was water. The mass gain was assessed at different intervals, and the experimental data were fitted to the Fick model considering the berries as spheres. Six empirical/semi-empirical models describing the diffusion of water during drying were used to predict the rehydration process. Fick’s law satisfactorily represented the data, and the highest diffusion coefficients were found when the berries were rehydrated in water at 45°C. Rehydration of berries in milk resulted in nutrient gain as different diffusive flows occurred during the process. The use of empirical models to predict the operating time of the rehydration processes allows flexibility as such models are mathematically simpler than the Fick model. Diffusivity is essential for the design/construction of equipment, and/or process optimization and implementation.